1988
DOI: 10.1161/01.cir.78.3.566
|View full text |Cite
|
Sign up to set email alerts
|

Potential protective effect of high coronary wedge pressure on left ventricular function after coronary occlusion.

Abstract: To assess the potential of coronary collateral circulation to protect myocardium after occlusion of a coronary vessel, the mean coronary wedge pressure, the angiographic grade of Experimentally, the coronary collateral circulation has been studied mainly in the dog heart. Because collaterals are more developed in dogs than in healthy humans, the results can not necessarily be extrapolated to the human coronary circulation. The hemodynamics of coronary collaterals have been studied directly in humans during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 31 publications
(14 reference statements)
1
6
0
1
Order By: Relevance
“…It is also important to note that this relative expression of collateral flow seems more relevant than absolute collateral flow, as myocardial distribution area is unknown and varies widely in different arteries and different patients. Pijls et al [8] have found that the value of 0.30 may differentiate between patients with sufficient and insufficient recruitable collateral flow, which was very similar to previous findings of P w /P a of 0.30 and 0.31 [17,19,20]. In addition, Sieler et al [22] have shown that using collateral flow index using velocity measurement, the value of 0.30 also discriminate patients with sufficient collaterals with 100% sensitivity and 93% specificity.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…It is also important to note that this relative expression of collateral flow seems more relevant than absolute collateral flow, as myocardial distribution area is unknown and varies widely in different arteries and different patients. Pijls et al [8] have found that the value of 0.30 may differentiate between patients with sufficient and insufficient recruitable collateral flow, which was very similar to previous findings of P w /P a of 0.30 and 0.31 [17,19,20]. In addition, Sieler et al [22] have shown that using collateral flow index using velocity measurement, the value of 0.30 also discriminate patients with sufficient collaterals with 100% sensitivity and 93% specificity.…”
Section: Discussionsupporting
confidence: 60%
“…The importance and protective role of collateral circulation has been appreciated both experimentally, as well as in the clinical settings [16][17][18][19][20]. Its clinical usefulness, however, has been limited probably because of two reasons: [1] no reliable quantitative method for evaluation of collateral circulation was available, and [2] clinical focus on treatment of coronary stenosis, with exponential rise and clinical interest in angioplasty over evaluation of coronary physiology.…”
Section: Discussionmentioning
confidence: 99%
“…The very low values of coronary pressure during balloon occlusion, however, suggest the lack of significant collateral circulation. 38 Moreover, the finding of decreased coronary…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Coronary collaterals are 40 μm in diameter and are not angiographically visible in normal conditions (22). They are angiographically demonstrable only if severe CAD is present due to increased blood flow associated with pressure gradient (23).…”
Section: Discussionmentioning
confidence: 99%